2020
DOI: 10.3390/jcm9103077
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Thrombin Calibration Algorithms and Correction for Thrombin-α2macroglobulin Activity

Abstract: Background: The thrombin generation (TG) test is useful for characterizing global hemostasis potential, but fluorescence substrate artifacts, such as thrombin-α2macroglobulin (T-α2MG) signal, inner filter effect (IFE), substrate consumption, and calibration algorithms have been suggested as sources of intra- and inter-laboratory variance, which may limit its clinical utility. Methods: Effects of internal vs. external normalization, IFE and T-α2MG on TG curves in normal plasma supplemented with coagulation fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 42 publications
(125 reference statements)
3
16
0
Order By: Relevance
“…Similarly, Hemker and Kremers 23 previously suggested that the TG assay performance is not affected by the calculation method but rather by the preanalytical treatment of the sample, that is, removing cell material when preparing plasma, and insufficient temperature control. However, Hemker and Kremers’s conclusions about the calculation methods do not apply to severely procoagulant samples, such as those with elevated prothrombin (this work) and antithrombin deficiency 12,15 …”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Similarly, Hemker and Kremers 23 previously suggested that the TG assay performance is not affected by the calculation method but rather by the preanalytical treatment of the sample, that is, removing cell material when preparing plasma, and insufficient temperature control. However, Hemker and Kremers’s conclusions about the calculation methods do not apply to severely procoagulant samples, such as those with elevated prothrombin (this work) and antithrombin deficiency 12,15 …”
Section: Discussionmentioning
confidence: 91%
“…This study is the extension of the previous computational work comparing algorithms for TG assay analysis 15 . Both studies are based on a reanalysis of the raw experimental data generated in TG experiments performed previously 16 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations